2015
DOI: 10.1007/s00406-015-0616-y
|View full text |Cite
|
Sign up to set email alerts
|

Attentional dysfunction in abstinent long-term cannabis users with and without schizophrenia

Abstract: Long-term cannabis use may confer cognitive deficits and increased risk of psychosis. However, the relationship between cannabis use and schizophrenia is complex. In particular, little is known about the effects of chronic cannabis use on the attention-related electric brain response in schizophrenia. We investigated auditory novelty and oddball P300 evoked potentials in a mixed sample of first-episode and chronic schizophrenic patients and healthy controls with (SZCA, n = 20; COCA, n = 20, abstinence ≥28 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 85 publications
0
2
0
2
Order By: Relevance
“…A number of distinct electrophysiological alterations have also been noted in P-C versus P-NC indicating pre-attentional, attentional and reward cue deficits. Although one study demonstrated no differences between cannabis-using and non-using patients, in P50 sensory gating (Rentzsch et al, 2007), differences have been demonstrated in prepulse inhibition (PPI) with relative sparing of the diminished PPI amplitude seen in P-NC; (Morales-Muñoz et al, 2015; Scholes-Balog and Martin-Iverson, 2011); reduced P300 amplitudes for P-C versus P-NC to novelty and oddball auditory stimuli (Rentzsch et al, 2016), modulation of mismatch negativity (MMN) (Pesa et al, 2012; Rentzsch et al, 2011) and altered late positive potential to reward cues such that there appears to be blunting of response to natural but not cannabis visual cues in the P-C group (Cassidy et al, 2014). MMN is believed to index glutamatergic function and is discussed further below (see III(iii)).…”
Section: Introductionmentioning
confidence: 99%
“…A number of distinct electrophysiological alterations have also been noted in P-C versus P-NC indicating pre-attentional, attentional and reward cue deficits. Although one study demonstrated no differences between cannabis-using and non-using patients, in P50 sensory gating (Rentzsch et al, 2007), differences have been demonstrated in prepulse inhibition (PPI) with relative sparing of the diminished PPI amplitude seen in P-NC; (Morales-Muñoz et al, 2015; Scholes-Balog and Martin-Iverson, 2011); reduced P300 amplitudes for P-C versus P-NC to novelty and oddball auditory stimuli (Rentzsch et al, 2016), modulation of mismatch negativity (MMN) (Pesa et al, 2012; Rentzsch et al, 2011) and altered late positive potential to reward cues such that there appears to be blunting of response to natural but not cannabis visual cues in the P-C group (Cassidy et al, 2014). MMN is believed to index glutamatergic function and is discussed further below (see III(iii)).…”
Section: Introductionmentioning
confidence: 99%
“…THC administration in healthy subjects weakens the P300 response recorded from midline frontal, central, and parietal electrodes during a choice reaction task, indicating the involvement of the eCB system in attention and working memory (Roser et al, 2008). Weak P300 has also been shown in chronic cannabis users (Rentzsch et al, 2016) which however manifest increased P300 amplitude when exposed to unpleasant trait words, and decreased negative symptoms such as affective blunting (Skosnik et al, 2008). These findings suggest that the eCB system may be particularly relevant for the positive symptoms of schizophrenia.…”
Section: The Ecb System In Schizophrenia: Specific Functional Alteratmentioning
confidence: 98%
“…Murray ve arkadaşları (2017) da yapmış oldukları çalışmada, esrar kullanımının psikotik belirtiler ve şizofreni benzeri psikoz riskinin artışı ile ilişkili olduğunu saptamışlardır (4). Uzun süren esrar kullanımının sağlıklı bireylerde dahi nörobilişsel yapıda bozulmalara sebep olduğu ve psikoz riskini arttırdığı kanıtlanmıştır (7). Bu oturumların uygulandığı süreçte bireyin maddeyi mantığa uygunlaştırma çabası, anne baba tutumunun aşırı izin verici olması, paranoid düşünce eğilimi, konsantrasyonda azalma ve sorumluluk almama gibi özelliklerinden dolayı danışana "bireysel baş etmede yetersizlik" hemşirelik tanısı konmuştur.…”
unclassified
“…Murray ve arkadaşları (2017) da yapmış oldukları çalışmada, esrar kullanımının psikotik belirtiler ve şizofreni benzeri psikoz riskinin artışı ile ilişkili olduğunu saptamışlardır (4). Uzun süren esrar kullanımının sağlıklı bireylerde dahi nörobilişsel yapıda bozulmalara sebep olduğu ve psikoz riskini arttırdığı kanıtlanmıştır (7).…”
unclassified